Effects of Marital Status and Social Support on Antenatal Depression: A Meta-Analysis - Meita Tyas Nugrahaeni; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Pregnancy is a period of increased vulnerability to depression incidence, especially if the pregnancy is accompanied by additional demands. Antenatal depression is depression that occurs during pregnancy characterized by certain symptoms, namely anxiety, distress, confusion, and excessive fear. The study aims to estimate the effect size of marital status and social support on the incidence of antenatal depression in pregnant women. Subjects and Method: The study used systematic review and meta-analysis with PICO, Population: pregnant women; Intervention: marital status and strong social support; Comparison: unmarried marital status and weak social support. Outcome: antenatal depression. The articles used were obtained from several databases namely Google Scholar, Pubmed, SpringerLink, and Science Direct. The article search keywords were